2012
DOI: 10.1186/1471-2458-12-1116
|View full text |Cite
|
Sign up to set email alerts
|

Environmental correlates of crimean-congo haemorrhagic fever incidence in Bulgaria

Abstract: BackgroundCrimean-Congo Haemorrhagic Fever (CCHF) is a zoonotic viral disease transmitted by ixodid tick bites, mainly of Hyalomma spp., or through contact with blood/tissues from infected people or animals. CCHF is endemic in the Balkan area, including Bulgaria, where it causes both sporadic cases and community outbreaks.MethodsWe described trends of CCHF in Bulgaria between 1997 and 2009 and investigated the associations between CCHF incidence and a selection of environmental factors using a zero-inflated mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
40
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 35 publications
14
40
0
2
Order By: Relevance
“…This result is similar to previous studies in Iran, Turkey, and Bulgaria [3,6,11] and corresponds closely with the months that the temperature is between 30°C and 40°C and maximum humidity is between 20% and 50% (the favorite condition of Hyalomma ticks) in southeast Iran. It should be noted that the pattern of CCHF distribution on the other side of the border (in the Baluchistan province of Pakistan) is somewhat different from the results of our study, with two annual surges in April and August [20] and very few cases seen during the rest of the year.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result is similar to previous studies in Iran, Turkey, and Bulgaria [3,6,11] and corresponds closely with the months that the temperature is between 30°C and 40°C and maximum humidity is between 20% and 50% (the favorite condition of Hyalomma ticks) in southeast Iran. It should be noted that the pattern of CCHF distribution on the other side of the border (in the Baluchistan province of Pakistan) is somewhat different from the results of our study, with two annual surges in April and August [20] and very few cases seen during the rest of the year.…”
Section: Discussionsupporting
confidence: 91%
“…This result is somewhat similar to a previous study conducted in Bulgaria that described the trends of CCHF between 1997 and 2009 [6]. However, in a Turkish study, the number of cases increased dramatically from 2004 to 2007 [3].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…CCHF is considered endemic in several parts of the Balkans, with over 1,500 human cases registered in Bulgaria up to 2009 [17,18]. Seroprevalence studies have shown human exposure to CCHFV in numerous districts across the country, with the highest rates in the Burgas region, where the UK traveller in this report was based [19].…”
Section: Discussionmentioning
confidence: 94%
“…CCHF is endemic in Europe and Bulgaria however outbreaks have been recorded in other countries like Kosovo, Turkey, Albania, Ukraine and South-west of the Russian Federation with increased number of cases . In Bulgaria, totally 159 CCHF cases were identified between 1997 and 2009 (Vescio et al, 2012). Between 2002 and 2009 increased numbers of CCHF cases were reported from Turkey (Ozdarendeli et al, 2010).…”
Section: Epidemiologymentioning
confidence: 99%